Intra-African Trade in the Context of Globalization: A Re-examination of the ECOWAS Protocol on Trade Liberalization - Onyia, Fredrick O. (Richtmann Publishing, 2020)
The Protocol on Trade Liberalization is one of the first five protocols that were originally annexed to the Treaty of ECOWAS. It was signed at Lome, Togo on November 5th 1976. To give further impetus to the Protocol, the Authority of Heads of States and Government at a summit held in Dakar, Senegal from July 25-27, 1992 adopted some modifications of the Trade Liberalization Scheme. With the sweeping torrent of Globalization, ECOWAS member-states have found themselves in a dilemma. The dilemma arises from the fact that pursuing the goals of integration and at the same time embracing the gains of globalization creates a paradox. The study investigates whether ECOWAS Protocol on Trade Liberalization enhanced intra-African trade more than trade with third countries with the emergence of globalization. It is anchored on the neo-functionalist theory and made use of documentary method of data collection. The study contends that intra-African trade within ECOWAS has declined with globalization while trade with third countries has increased. The implication is that the stimulation and synergy of economies of member-states which Trade Liberalization is supposed to engender has been weakened. The study recommends a further revision of the provisions of the Trade Liberalization scheme by ECOWAS member states to align with the emerging realities of globalization. It further recommends the improvement of transportation infrastructure in the sub-region and mustering of political will by the leaders to implement their resolutions, among others.